Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and hyperuricemia: evidence from the CHARLS study - Hou, Xin; Zhu, Zhenghao; Chen, Xinmin; Li, Yanhui; Feng, Guofeng; Zhou, Xiangjie; Gong, Zheng; Yang, Yang; Zhang, Xiaohong (Frontiers in Nutrition, 2025)
Background and aimsThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is an innovative composite lipid measure. This study aims to examine the correlation between NHHR and hyperuricemia in the middle-aged and elderly demographic in China.MethodsThis investigation comprised 4,639 individuals who were devoid of hyperuricemia at baseline in 2011, utilizing data from the China Health and Retirement Longitudinal Study (CHARLS). We utilized multivariable logistic regression, restricted cubic spline (RCS) analysis, and subgroup analysis to investigate the relationship between NHHR and hyperuricemia.ResultsA total of 499 participants (10.76%) experienced hyperuricemia at the 4-year follow-up. The incidence of hyperuricemia was 176% higher for participants in the highest quartile of NHHR than for those in the lowest quartile (OR 2.76, 95% CI 2.10–3.62, p < 0.001). The risk of hyperuricemia was 64% higher in the highest quartile of NHHR than in the lowest quartile in a fully adjusted model (OR 1.64, 95% CI 1.16–2.31, p = 0.005). The risk of hyperuricemia and NHHR had a linearly positive connection, according to restricted cubic spline (RCS) analysis (P for non-linearity > 0.05). Subgroup analysis showed that among women, non-smokers, and those over 60, the relationship between NHHR and hyperuricemia was more significant.ConclusionNHHR and hyperuricemia have a substantial linear positive connection, indicating that NHHR might be used as a tool for assessing hyperuricemia risk and offering valuable information for both prevention and therapy.